Issues applied linguistics - McCarthy, Michael (Cambridge University Press, 2001)
This book provides a wide-ranging and comprehensive treatment of the major issues in applied linguistics. It outlines the historical roots of the field and its major developments over the years, and examines current issues such as language modeling and the analysis of discourse.